2018
DOI: 10.1016/j.dib.2018.10.111
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of heavy metals (Ni, Cd, Pb) by Azolla filiculoides from aqueous solution: A dataset

Abstract: In this article, the data of heavy metals phytoremediation efficiency were provided. The Azolla was collected from the lake around the Rasht city and washed in tap water, then weighed (0.2, 0.4 and 0.8 g), and kept for 15 days in the 100 ml disposable container in the presence 5, 10 and 25 mg/L of lead, nickel and cadmium ions. The samples were stored in polyethylene containers for analysis of the metal concentration with ICP-OES. According to the results, removal efficiency was increased from 40% to 70% at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The ability of A. filiculoides to accumulate heavy metals from treating solutions has been highlighted in several studies. For example, treatments of A. filiculoides with solutions containing Ni, Cd and Pb- cations (5, 10 and 25 mg/L) showed an increased removal efficiency (from 40 up to 70%) by increasing the contact time up to 10 days [ 40 ]. Khosravi et al [ 49 ] revealed that living samples of A. filiculoides were able to remove Pb 2+ , Cd 2+ , Ni 2+ and Zn 2+ from aqueous solutions enriched by 4 mg/L of metal ions and their presence caused up to 42% inhibition of biomass growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of A. filiculoides to accumulate heavy metals from treating solutions has been highlighted in several studies. For example, treatments of A. filiculoides with solutions containing Ni, Cd and Pb- cations (5, 10 and 25 mg/L) showed an increased removal efficiency (from 40 up to 70%) by increasing the contact time up to 10 days [ 40 ]. Khosravi et al [ 49 ] revealed that living samples of A. filiculoides were able to remove Pb 2+ , Cd 2+ , Ni 2+ and Zn 2+ from aqueous solutions enriched by 4 mg/L of metal ions and their presence caused up to 42% inhibition of biomass growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this nitrogen-fixing ability, it can be used also to stimulate the growth of crops in water (e.g., rice) [ 38 ]. Furthermore, thanks to its ability in removing heavy metals and other contaminants (e.g., azo dyes, hydrazine) from the aquatic environment, this species has been studied for potential applications in phytoremediation processes [ 39 , 40 , 41 , 42 , 43 ]. In addition, it has been employed as a non-target organism to detect the potential effects of pharmaceuticals released in the aquatic environment [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have used both whole plants (e.g. Lemna gibba (Morales-Barrera et al 2020), Azolla filiculoides (Naghipour et al 2018), Pistia stratiotes or Nymphaea lotus (Ugya et al 2019)) and various plant fragments in their studies. For nickel sorption, both plant parts such as bark (Cancelo-Gonza ´lez et al 2017;Akar et al 2019) or cones (Oguz 2020), and more fragmented parts such as fibers (Boudaoud et al 2017), bagasse (Rico et al 2018;Candelaria et al 2019) and sawdust (Richard et al 2020) were used.…”
Section: Trends In Biosorbent Researchmentioning
confidence: 99%
“…In particular, Azolla filiculoides has been chosen due to its high biomass production, metal accumulation ability (Valderrama et al 2013;Naghipour et al 2018) and free floating nature, all positive characteristics for phytoremediation purposes. In addition, the high water content typical of A. filiculoides fronds (Serag et al 2000) drastically reduces the problems of disposal (Sood et al 2012) and its ability to make symbiotic relationship with the heterocystous blue-green alga, Anabaena azollae, allows its growth also in contaminated low nitrogen environment.…”
Section: )mentioning
confidence: 99%